(untitled) (Materiali di Estetica. Terza serie, 2019)
In our digital era there is urgent need to get acquainted with new methodologies in order to improve educational processes in the Humanities. As a result researches upon Didactics are at their peak. Since 2000 competence-oriented, intercultural, intermedial and interdisciplinary teaching in German Literature has become more and more required. Karlheinz Fingerhut has payed all his life long particular attention to literaricity and to aesthetic education, also pursuing linguistic aims such as fostering foreign-language competences and intercultural understanding. He has structured his works focusing on innovative approaches without forgetting curricular, textual-thematic and functional-discursive dimensions corresponding to the new curricular vision of global competences. The present paper is aimed at investigating how much influence his researches continue to exert in our digital era, in which world academicians are engaged with passing on the heritage of literaricity while inventing the future. Karlheinz Fingerhut was and remains one of the most engaged scholars in the research field: of the Didactics of German Literature. His books as well as his studies have contributed to write the new instructional programs after Bologna and PISA. His last work – Kafka für Querdenker / Kafka for Lateral Thinkers - offers a broad range of the newest methodological instruments to teach German Literature in order to improve close-reading; heuristic reading as well as productive writing. Thanks to Karlheinz Fingerhut students are given the opportunity to cope with different media for the learning of German Literature in order to grow both as responsible citizens of the world and as individual persons. The present contribution is devoted to his memory, his work and researches.